2019
DOI: 10.1002/nme.6091
|View full text |Cite
|
Sign up to set email alerts
|

Efficient and accurate stress recovery procedure and a posteriori error estimator for the stable generalized/extended finite element method

Abstract: Summary This paper presents a new stress recovery technique for the generalized/extended finite element method (G/XFEM) and for the stable generalized FEM (SGFEM). The recovery procedure is based on a locally weighted L2 projection of raw stresses over element patches; the set of elements sharing a node. Such projection leads to a block‐diagonal system of equations for the recovered stresses. The recovery procedure can be used with GFEM and SGFEM approximations based on any choice of elements and enrichment fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
31
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 9 publications
(31 citation statements)
references
References 38 publications
0
31
0
Order By: Relevance
“…In addition, available extensions of the ZZ estimator to the G/XFEM have already shown that different basis functions can be used to generate the displacement and the recovered stress fields. For instance, Bordas and Duflot 34 and Bordas et al 35 used Westergaard solutions to generate a basis that approximates the near-tip recovered strain field, and Prange et al 31 and Lins et al 32,33 used the asymptotic near-tip stress field, that is, the stresses of a problem consisting of a crack inserted in an unbounded domain, to write the recovered stress field. It is noted that the methods presented in those works [31][32][33][34][35] are first-order.…”
Section: Zz-bd Recovery Procedures and Error Estimatormentioning
confidence: 99%
See 3 more Smart Citations
“…In addition, available extensions of the ZZ estimator to the G/XFEM have already shown that different basis functions can be used to generate the displacement and the recovered stress fields. For instance, Bordas and Duflot 34 and Bordas et al 35 used Westergaard solutions to generate a basis that approximates the near-tip recovered strain field, and Prange et al 31 and Lins et al 32,33 used the asymptotic near-tip stress field, that is, the stresses of a problem consisting of a crack inserted in an unbounded domain, to write the recovered stress field. It is noted that the methods presented in those works [31][32][33][34][35] are first-order.…”
Section: Zz-bd Recovery Procedures and Error Estimatormentioning
confidence: 99%
“…Following the strategy proposed by Lins et al, 33 the right-hand side entries b d 𝛽j can first be reinterpreted as an L 2 inner product between σd (x) and  d 𝛽j (x), locally weighted by the PoU 𝜑 𝛽 (x), that is,…”
Section: A Block Diagonalization Techniquementioning
confidence: 99%
See 2 more Smart Citations
“…later adapted this approach to improve the stress field within stable GFEM (SGFEM); because SGFEM modifies the X/GFEM enrichment functions to solve the issue of ill‐conditioned stiffness matrices, 46‐48 the enrichment functions used to interpolate the recovered stress field are also modified. Instead of using a global least squares projection, Lins et al 49 . proposed a more computationally efficient recovery technique, whereby a consistent block‐diagonal projection operator 50 is used to perform a locally weighted least squares projection of directly‐calculated stresses over patches of elements.…”
Section: Introductionmentioning
confidence: 99%